A 'speculative pasts' pedagogy: where speculative design meets historical thinking. Issue 4 (2nd October 2019) - Nooney, Laine; Brain, Tega
ABSTRACT: This paper provides a pedagogic context for the authors' concept of 'Speculative Pasts, ' framed within an auto-ethnographic account of their co-taught course 'How the Computer Became Personal.' Blending disciplinary methodologies from historical practice and speculative and critical design, the Speculative Pasts assignment asks students to create primary documents from a hypothetical historical scenario related to an aspect of American personal computing history. This paper lays out the disciplinary contexts and development process for working across design and history disciplines, curricular organization, assignment process, and offers analysis of examples from student work. Additionally, this paper details how 'Speculative Pasts' offer a critique of the narrowness and problematic futurism of 'speculative futures.' Altogether, the authors offer this course and its primary project as a model for making history essential, rather than supplementary, to design and for leveraging practice-based production as a valued mode of historical inquiry.